2005
DOI: 10.1002/ajim.20249
|View full text |Cite
|
Sign up to set email alerts
|

Workplace air quality and lung function among dental laboratory technicians

Abstract: Workplace PM2.5 was associated with a non-significant decrease in lung function of dental technicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
(23 reference statements)
0
17
2
3
Order By: Relevance
“…In two other studies on dental technicians, it was reported that that there were restrictive pulmonary disorders in 22.4% and 33.3% of participants (17,25). In another two studies, it was reported that there was a decrease in FVC and FEV 1 levels and that longer working durations led to worse PFT values (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…In two other studies on dental technicians, it was reported that that there were restrictive pulmonary disorders in 22.4% and 33.3% of participants (17,25). In another two studies, it was reported that there was a decrease in FVC and FEV 1 levels and that longer working durations led to worse PFT values (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The data related to airway interactions in the dental technicians are controversial. Woan et al conducted a study on 11 dental technicians in Taiwan whom they studied for more than 10 years, and they found a small decrease in FVC and FEV 1 when compared with the control group, which is statistically not important [1]. Choudat et al performed a study in which they examined respiratory symptoms and lung functions on 105 dental technicians living in Paris [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in the literature demonstrate potential hazards for dental technicians related to their working conditions [1][2][3][4][5][6][15][16][17][18][19][20][21][22][23][24]. Most of the studies have related to the determination of the prevalence of pneumoconiosis such as our first cross-sectional epidemiologic study [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again this is thought to be related to dust inhalation (Sherson et al, 1988;Choudat et al, 1993;Jacobsen and Pettersen 1993;Selden et al, 1995;Jacobsen et al, 1996;Kim et al, 2002;Radi et al, 2002;Hu et al, 2006). Lung biopsies of dental technicians have found fibrosis, dust accumulations, inorganic material and very high concentrations of fibres within the sampled tissue (Tuengerthal et al, 1983).…”
Section: Introductionmentioning
confidence: 99%